Triptycene scaffolds: Synthesis and properties of triptycene-derived Schiff base compounds for the selective and sensitive detection of CN− and Cu2+. Issue 20 (18th May 2017) - Emandi, Ganapathi; Browne, Michelle P.; Lyons, Michael E.; Prior, Caroline; Senge, Mathias O.
Abstract: A series of triptycene-derived Schiff bases were synthesized by condensation between amino triptycenes with an appropriate aldehyde and were isolated in good to excellent (85–90%) yields. Amongst these, a triptycene-hydroxybenzaldehyde Schiff base compound proved to be a selective sensor for cyanide. It exhibited a "turn-on" fluorescence response at 490 nm to CN − facilitated by the nucleophilic addition of CN − to the aldehyde group, accompanied by a visible color change from orange to yellow. Likewise, a triptycene salicylaldehyde adduct was shown to be highly sensitive towards the detection of the CN − ion with a detection limit of 0.9 μM. On the other hand a triptycene-BODIPY Schiff base compound could be used for the detection of Cu 2+ ions over other competing, biologically relevant metal ions in acetonitrile. Photophysical studies revealed a 1:1 binding model for the triptycene-BODIPY compound. Graphical abstract: